Germplasm acquisition and distribution by CGIAR Genebanks - Halewood, Michael; Jamora, Nelissa; Noriega, I.L.; Anglin, Noelle L.; Wenzl, Peter; Payne, T.; Ndjiondjop, M.N.; Guarino, Luigi; Kumar, P. Lava; Yazbek, M.; Muchugi, A.; Azevedo, Vania; et al. (MDPI, 2020)
The international collections of plant genetic resources for food and agriculture (PGRFA) hosted by 11 CGIAR Centers are important components of the United Nations Food and Agriculture Organization’s global system of conservation and use of PGRFA. They also play an important supportive role in realizing Target 2.5 of the Sustainable Development Goals. This paper analyzes CGIAR genebanks’ trends in acquiring and distributing PGRFA over the last 35 years, with a particular focus on the last decade. The paper highlights a number of factors influencing the Centers’ acquisition of new PGRFA to include in the international collections, including increased capacity to analyze gaps in those collections and precisely target new collecting missions, availability of financial resources, and the state of international and national access and benefit-sharing laws and phytosanitary regulations. Factors contributing to Centers’ distributions of PGRFA included the extent of accession-level information, users’ capacity to identify the materials they want, and policies. The genebanks’ rates of both acquisition and distribution increased over the last decade. The paper ends on a cautionary note concerning the potential of unresolved tensions regarding access and benefit sharing and digital genomic sequence information to undermine international cooperation to conserve and use PGRFA.